2011
DOI: 10.1007/s11255-011-0082-z
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferases T1 null genotype is associated with susceptibility to aristolochic acid nephropathy

Abstract: This study supports the hypothesis that polymorphisms related to drug metabolism such as GSTT1 may be an important factor influencing the development of AAN in the Chinese Han population exposed to AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…And the associations between common genotypes of CYP1A1, NQO1 (NAD (P)H quinone oxidoreductase 1), MDR1 (P-glycoprotein) and glutathione S-transferase (GST) and AAN risk were investigated. Results found that only GST null genotype was related to AAN susceptibility (Chen et al, 2012). In this study, we find that AAI is a substrate of BCRP.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…And the associations between common genotypes of CYP1A1, NQO1 (NAD (P)H quinone oxidoreductase 1), MDR1 (P-glycoprotein) and glutathione S-transferase (GST) and AAN risk were investigated. Results found that only GST null genotype was related to AAN susceptibility (Chen et al, 2012). In this study, we find that AAI is a substrate of BCRP.…”
Section: Discussionsupporting
confidence: 53%
“…The interaction between AAI and intestinal efflux drug transporters has not been investigated yet. Chen et al reported that there was no relationship between MDR1 polymorphism and AAN risk (Chen et al, 2012), which could not prove whether AAI was a substrate of MDR1.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These genetic variations appear to be important determinants of cancer risk or other toxic effects of many xenobiotics (Stiborová et al 2008a , b , 2009 ). The combination of polymorphic enzymes along with environmental exposure to AA may result in an increased risk for the development of BEN/AAN (Atanasova et al 2005 ; Toncheva et al 2004 ; Toncheva 2006 ; Chen et al 2012a ). Hence, research over the last two decades has aimed to identify the enzymes principally involved AA metabolism (reviewed in Stiborová et al 2008a , b , 2009 , 2013b , 2014a , c , 2015b ).…”
Section: Metabolism Of Aristolochic Acidmentioning
confidence: 99%
“…However, not all individuals exposed to AA are susceptible to develop AAN. Chen 15 suggested that glutathione s-transferases T1 null genotype is associated with susceptibility to aristolochic acid nephropathy.…”
Section: Discussionmentioning
confidence: 99%